Future Distribution of Abramis brama (Linnaeus, 1758) under Climate Change scenarios - N. Tabasinezhad; H. Mosavi-Sabet; H. Mostafavi (Iranian Journal of Applied Ecology)
Riverine ecosystems and aquatic animals have suffered many pressures due to the increase of human industrial activities and subsequent climate changes. In the present study, changes in the distribution range of the bream fish (Abramis brama) inhabiting the rivers of the southern Caspian Sea basin in the years 2050 and 2080 under optimistic and pessimistic climate scenarios were assessed by using the MaxEnt model. This study utilized datasets collected by the authors and various scientific resources available over 50 years (1970-2020). According to the receiver operating characteristics curve, and area under curve (AUC), the model performance in predicting species distribution was excellent (AUC = 0.947). Furthermore, modeling results indicated a significant likely decrease in the distribution of this species under both optimistic and pessimistic scenarios, in both periods of 2050 and 2080, with the highest predicted reduction percentage of 98.71% under the pessimistic scenario in 2080. Given the importance of the bream fish in the food chain and its positive impact on the economy and livelihoods of local communities, conservation efforts such as preventing overfishing, developing conservation strategies to cope with future events, and striving to reduce climate change accelerators are recommended for the protection of this valuable species.